Cell-in-Cell Phenomenon and Its Relationship With Tumor Microenvironment and Tumor Progression: A Review - Wang, Xinlong; Li, Yilong; Li, Jiating; Li, Le; Zhu, Hong; Chen, Hua; Kong, Rui; Wang, Gang; Wang, Yongwei; Hu, Jisheng; Sun, Bei (Frontiers in Cell and Developmental Biology, 2019)
The term cell-in-cell, morphologically, refers to the presence of one cell within another. This phenomenon can occur in tumors but also among non-tumor cells. The cell-in-cell phenomenon was first observed 100 years ago, and it has since been found in a variety of tumor types. Recently, increasing attention has been paid to this phenomenon and the underlying mechanism has gradually been elucidated. There are three main related process: cannibalism, emperipolesis, and entosis. These processes are affected by many factors, including the tumor microenvironment, mitosis, and genetic factors. There is considerable evidence to suggest that the cell-in-cell phenomenon is associated with the prognosis of cancers, and it promotes tumor progression in most situations. Notably, in pancreatic cancer, the cell-in-cell phenomenon is associated with reduced metastasis, which is the opposite of what happens in other tumor types. Thus, it can also inhibit tumor progression. Studies show that cell-in-cell structure formation is affected by the tumor microenvironment, and that it may lead to changes in cellular characteristics. In this review, we summarize the different cell-in-cell processes and discuss their role in tumor progression and how they are regulated by different mechanisms.